The importance of solid electrolyte interphase formation for long cycle stability full-cell Na-ion batteries. (September 2016) - Li, Xiaolin; Yan, Pengfei; Engelhard, Mark H.; Crawford, Alasdair J.; Viswanathan, Vilayanur V.; Wang, Chongmin; Liu, Jun; Sprenkle, Vincent L.
Abstract: Na-ion battery, as an alternative high-efficiency and low-cost energy storage device to Li-ion battery, has attracted wide interest for electrical grid and vehicle applications. However, demonstration of a full-cell battery with high energy and long cycle life remains a significant challenge. Here, we investigated the role of solid electrolyte interphase (SEI) formation on both cathodes and anodes and revealed a potential way to achieve long-term stability for Na-ion battery full-cells. Pre-cycling of cathodes and anodes leads to preformation of SEI, and hence mitigates the consumption of Na ions in full-cells. The example full-cell of Na0.44 MnO2 -hard carbon with pre-cycled and capacity-matched electrodes can deliver a specific capacity of 116 mAh/g based on Na0.44 MnO2 at 1 C rate (1 C=120 mA/g). The corresponding specific energy is 313 Wh/kg based on the cathode. Excellent cycling stability with 77% capacity retention over 2000 cycles was demonstrated at 2 C rate. Our work represents a leap forward in Na-ion battery development. Graphical abstract: Highlights: Na0.44 MnO2 -hard carbon full-cell shows 77% capacity retention over 2000 cycles at 2C rate. Based on the cathode, it has 116 mAh/g capacity and 313 Wh/kg specific energy at 1C rate. The importance of solid electrolyte interphase to the full-cell performance was demonstrated.